Awards and rewards: Evidence from an evaluation of the Metrobank's search for outstanding teachers - Majah-Leah V. Ravago; Dennis S. Mapa (University of the Philippines, School of Economics (UPSE), 2017)
We investigate the impact of the "Metrobank Award for Outstanding Teachers" using a unique dataset from a survey of teachers who competed from 1988 to 2010. Our study is one of the firsts to use income as the primary indicator of success. When the sample is limited to those who were actively teaching in 2014, we find that the Award had a higher impact on awardees who were relatively younger. The intuitive explanation is that "younger" awardees have more years in their career to capitalize on the Award.
Keywords: A20; C40; I21; I20; 330; Impact evaluation; RDD; awards; teacher's professional trajectory